Telemedicine services for living kidney donation: A US survey of multidisciplinary providers. Issue 8 (31st May 2022) - Al Ammary, Fawaz; Motter, Jennifer D.; Sung, Hannah C.; Lentine, Krista L.; Sharfuddin, Asif; Kumar, Vineeta; Yadav, Anju; Doshi, Mona D.; Virmani, Sarthak; Concepcion, Beatrice P.; Grace, Terry; Sidoti, Carolyn N.; et al.
Abstract : Individuals considering living kidney donation face geographic, financial, and logistical challenges. Telemedicine can facilitate healthcare access/care coordination. Yet difficulties exist in telemedicine implementation and sustainability. We sought to examine centers' practices and providers' attitudes toward telemedicine to improve services for donors. We surveyed multidisciplinary providers from 194 active adult US living donor kidney transplant centers; 293 providers from 128 unique centers responded to the survey (center representation rate = 66.0%), reflecting 83.9% of practice by donor volume and 91.5% of US states/territories. Most centers (70.3%) plan to continue using telemedicine beyond the pandemic for donor evaluation/follow‐up. Video was mostly used by nephrologists, surgeons, and psychiatrists/psychologists. Telephone and video were mostly used by social workers, while video or telephone was equally used by coordinators. Half of respondent nephrologists and surgeons were willing to accept a remote completion of physical exam; 68.3% of respondent psychiatrists/psychologists and social workers were willing to accept a remote completion of mental status exam. Providers strongly agreed that telemedicine was convenient for donors and would improve the likelihood of completing donor evaluation. However, providers (65.5%) perceived out‐of‐state licensing as a key policy/regulatory barrier. These findings help inform practice and underscore the instigation of policies to remove barriers using telemedicine to increase living kidney donation. Abstract : A national survey of multidisciplinary providers regarding the use of telemedicine services for living kidney donor evaluation and care delineates center practices, provider attitudes, and perceived barriers including regulatory limitations of state licensing requirements.